PENGARUH KURS, INFLASI, SUKU BUNGA SBI DAN INDKS BURSA INTERNASIOAL TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK INDONESIA PERIODE 2014-2017 - Fatus All Anati; ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
Abstract This study aims to determine the effect of Exchange Rate, Inflation, SBI Interest Rate, and International Stock Index Against the Composite Stock Price Index. The analytical method used is a multiple linear regression analysis method carried out with the SPSS 14.0 program. this study uses monthly data for the 2014-2017 period on each research variable. The results of this study partially show that the exchange rate has a significant negative effect on the Composite Stock Price Index, Inflation has no significant effect on the direction of the Composite Stock Price Index, SBI Interest Rate does not significantly influence the negative direction of the Composite Stock Index, the Nikkei 225 Index has a negative effect significant to the Composite Stock Price Index, the Dow Jones Index has a significant positive effect on the Composite Stock Price Index.Keyword : Exchange Rate, Inflation, SBI Interest Rate, Nikkei 225 Index, Dow Jones Index, joint stock price index.